Coincidence of Condyloma Lata and Condyloma Acuminata in an HIV Infected Patient - Elita Nurhidayati; Putu Dyah Ayu Saraswati (Jurnal Impresi Indonesia, 2026)
Condyloma lata and condyloma acuminata are two distinct clinical manifestations caused by Treponema pallidum and low-risk human papillomavirus (HPV), respectively. While both are commonly encountered separately in individuals with high-risk sexual behavior, their coexistence in a single patient, particularly one with HIV infection, is rarely reported. We present the case of a 25-year-old man who has sex with men (MSM) and is living with HIV, presenting with multiple perianal lesions. Physical examination revealed verrucous, cauliflower-like growths and flat, moist erythematous plaques, consistent with condyloma acuminata and condyloma lata, respectively. Serologic tests were reactive for T. pallidum (TPHA positive, VDRL titer 1:32), supporting the diagnosis of active secondary syphilis. The patient, on regular antiretroviral therapy with a CD4 count of 350 cells/mm³, was treated with a single intramuscular injection of 2.4 million units of benzathine benzylpenicillin and received topical treatment for HPV-related lesions. Follow-up at four weeks demonstrated significant clinical improvement, along with a reduction in VDRL titer to 1:16. This case highlights the importance of clinical vigilance for multiple co-infections in immunocompromised patients and the need for thorough evaluation of overlapping anogenital lesions.